A three-dimensional mathematical model for drug delivery from drug-eluting stents - P. Darvishi; S. M. Salehi (Iranian Journal of Chemical Engineering)
Current drug-eluting stent (DES) technology is not optimized with regard to the pharmacokinetics of drug release, more research on the drug-eluting stent design and flux of drug release to the arterial wall is necessary. Considering a three-dimensional (3D) cylindrical mathematical model, a novel free drug mass transfer release has been formulated and applied for better estimation of the drug concentration in the tissue. The transport equations involved both convection and diffusion equations. Besides, a reversible reaction in the arterial wall was considered. The present model was solved by an appropriate numerical simulation method and the predicted results were compared with in vivo data. To find out the rate-limiting step, the time scale analysis was also applied. The obtained results showed that the binding process is more limited by convection and diffusion, where convection is the rate-controlling step. It is also demonstrated that the presented approach has advantages over the prior free drug mass transfer models, including better data prediction and satisfying mass transfer consistency.